2002
DOI: 10.1095/biolreprod66.2.486
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Irradiation Before Adulthood on Reproductive Function in the Male Rhesus Monkey1

Abstract: Today, many patients, who are often young, undergo total body irradiation (TBI) followed by bone marrow transplantation. This procedure can have serious consequences for fertility, but the long-term intratesticular effects of this treatment in primates have not yet been studied. Testes and epididymides of rhesus monkeys that received doses of 4-8.5 Gy of TBI at 2-4 yr of age were studied 3-8 yr after irradiation. In all irradiated monkeys, at least some seminiferous tubule cross-sections lacked germ cells, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 65 publications
3
47
1
2
Order By: Relevance
“…In humans and primates where spermatozoa may be isolated in testicular biopsies, it has been shown that recovery after severe damage occurs only focally in a few seminiferous tubules. Patients will be permanently infertile if tubules become fully hyalinized or a complete Sertoli cell only pattern is established (32,33). The spermatogenic stem cells are susceptible to this type of damaging insult at all ages, but the full impact on spermatogenesis manifests itself during onset of puberty (34).…”
Section: Differences In Germline Stem Cell Biology In Females and Malmentioning
confidence: 99%
“…In humans and primates where spermatozoa may be isolated in testicular biopsies, it has been shown that recovery after severe damage occurs only focally in a few seminiferous tubules. Patients will be permanently infertile if tubules become fully hyalinized or a complete Sertoli cell only pattern is established (32,33). The spermatogenic stem cells are susceptible to this type of damaging insult at all ages, but the full impact on spermatogenesis manifests itself during onset of puberty (34).…”
Section: Differences In Germline Stem Cell Biology In Females and Malmentioning
confidence: 99%
“…4 Gonadal exposure to ionizing radiation of the neonate, particularly preterm infants, is another important issue since irradiation before adulthood may have long-term harmful effects on the size and function of the gonads. [7][8][9] Detailed studies on the field size and body tissues included in each X-ray taken on these infants are scarce. 10 Considering the health hazards of ionizing radiation, the objective of this study was to evaluate unnecessary radiation exposure to body tissues outside the anatomical region of interest in five NICUs in Israel.…”
Section: Introductionmentioning
confidence: 99%
“…This finding indicates a critical role for spermatogonial stem cells in the restoration process. Functional proof for this is provided from germ cell transplantation experiments in mice and monkeys revealing that continuous recolonisation of remaining or reintroduced testicular stem cells leads to reinduction of spermatogenesis (Nagano and Brinster 1998;de Rooij et al 2002;Kamischke et al 2003). Therefore, spermatogonia are considered the selective target cells for the preservation of testis tissue and function, as well as for the development of novel options for fertility preservation in oncological patients (Nordhoff and Schlatt 2003;Orwig and Schlatt 2005).…”
Section: Spermatogonia: Target For Animal Conservation?mentioning
confidence: 99%